Selection mode of freight transport: waterways as a complement or alternative logistics modal for soya transportation in Mato Grosso - Valentini, Nicolò (2023)
Brazil's transportation infrastructure did not follow the country's agricultural development. As a matter of fact, the country is characterized by a distorted freight transportation matrix, in which road mode is predominant. This imbalance in the sector suggests the need to develop a more efficient transport network that can increase the utilization and the competitiveness of alternative modes, thus, facilitating the increasing flows of goods while reducing pollution. In that context, the purpose of this study is to assess the benefits of a modal shift from the current road transportation system to inland waterways for soya shipment throughout Mato Grosso from an economical and environmental perspective. To accomplish this task, two logistics solutions (BR-163 highway and Paraguay-Paraná river) have been considered to carry out the calculations on the overall transportation costs and CO2 emissions for each mode, assessing also the potential impacts from a multimodality approach between road and waterways. The findings suggest that the waterway presents itself as a valuable complement or alternative able to remarkably decrease logistic costs and greenhouse emissions due to its energy efficiency, greater productivity in relation to the cargo volumes, lower cost per ton.